2021
DOI: 10.1891/pa-d-20-0004
|View full text |Cite
|
Sign up to set email alerts
|

“I've Never Felt Such Absolute Devastating Loss”: A Photo Elicitation Exploration of Men's Postseparation Experiences of Coping After Intimate Partner Violence

Abstract: Current research and statistics support that there are a significant number of male victims of intimate partner violence (IPV), yet less is known about how men cope with, and indeed move on from, these experiences postseparation. The aim of the current study is to discuss the findings from a photo elicitation study exploring men's postseparation experiences of coping after IPV experiences; photo elicitation as a method of interviewing is simply the use of photos within an interview setting (Harper, 2002), they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 59 publications
0
1
0
Order By: Relevance
“…For example, work in the United States and Canada ( Dim, 2020 ; Hines & Douglas, 2010 ) and Europe ( Bates, 2019 ; Bjørnholt, & Rosten, 2020 ; Drijber et al, 2013 ; McCarrick et al, 2016 ) has shown that men’s victimization experiences may include physical and psychological forms of abuse. The physical assaults reported by male victims have been found to include serious physical attacks from their female partners including: hitting, stabbing with an object, kicking, biting, and choking ( Bates & Taylor, 2021 ; Machado et al., 2017 ). These assaults challenge the perception that women’s violence toward male partners is trivial and inconsequential ( James, 1996 ; Johnson, 2008 ; Saunders, 2002 ).…”
Section: Early Researchmentioning
confidence: 99%
“…For example, work in the United States and Canada ( Dim, 2020 ; Hines & Douglas, 2010 ) and Europe ( Bates, 2019 ; Bjørnholt, & Rosten, 2020 ; Drijber et al, 2013 ; McCarrick et al, 2016 ) has shown that men’s victimization experiences may include physical and psychological forms of abuse. The physical assaults reported by male victims have been found to include serious physical attacks from their female partners including: hitting, stabbing with an object, kicking, biting, and choking ( Bates & Taylor, 2021 ; Machado et al., 2017 ). These assaults challenge the perception that women’s violence toward male partners is trivial and inconsequential ( James, 1996 ; Johnson, 2008 ; Saunders, 2002 ).…”
Section: Early Researchmentioning
confidence: 99%